Effect of the COVID-19 pandemic on the mental health, daily and occupational activities of pediatric otolaryngologists in Latin America - Peñaranda, Augusto; Moreno-López, Sergio; Peñaranda, Daniel; Pérez-Herrera, Lucía C. (Frontiers in Public Health, 2022)
Background: Otolaryngologists have a higher risk of physical/psychological problems due to their frequent exposure to SARS-CoV-2. There is no information about the impact of COVID-19 on the mental health of these specialists in low/middle-income countries from Latin America. This study aimed to assess the frequency of anxiety, depression, and stress, as well as the changes in occupational and daily activities due to the COVID-19 pandemic in a group of pediatric otolaryngologists in Latin America. Methods: Observational, cross-sectional study conducted between October and December 2020. Mental health tools such as the Generalized Anxiety Disorder–7, the Patient Health Questionnaire-9, and the Perceived Stress Scale-10 were applied. Fear to COVID-19 scale and questionnaires about occupational and daily activities were also applied. Results: Among 55 pediatric otolaryngologists, the frequency of anxiety, depression, and stress were 67.3%, 45.5%, and 40%, respectively. Up to 27.3% of the specialists reported moderate to severe symptoms of anxiety, while 7.3% and 40% presented moderate depression and stress symptoms. The specialists reported a reduction of 58.3% of their consultations, as well as a 51.7% reduction in their monthly income compared to the same period before the pandemic. Up to 14.6% of the specialists expect to incorporate long-term (>1 year) drastic changes in their daily activities due to the pandemic. Conclusions: The frequency of anxiety, depression, and stress was high among pediatric otolaryngologists in Latin America compared to previous studies performed in high-income countries. Further research on these psychological outcomes is needed to achieve early mental health strategies.